Detection and correlation of changes on perimetry and optical coherence tomography in patients on chronic usage of hydroxychloroquine: A Cross-Sectional StudyDetection and Correlation of changes on Perimetry and Optical coherence tomography in patients on Chronic Usage of Hydroxychloroquine: A cross-sectional study - Yamini Priya; Puneeth Isloor; Usha Vasu; Sumithra Selvam; Vineeta Shobha (Indian Journal of Rheumatology)
Background: Early detection of retinal toxicity in patients on chronic usage of hydroxychloroquine (HCQ) and thereby the prevention of irreversible visual loss is an important goal. Methods: We performed a comprehensive ophthalmologic examination, visual field testing and macular scanning using spectral-domain optical coherence tomography (SD-OCT) and Humphrey Visual Field (HVF) 10-2 perimetry in chronic HCQ users (>1 year). Participants were grouped based on the duration of HCQ exposure (<2 years, 2–5 years; and >5 years) and compared all the ophthalmologic parameters between the groups. Results: We included 110 patients (68 rheumatoid arthritis and 42 systemic lupus erythematosus), mean age being 38.5 ± 8.9 years, and median cumulative HCQ dose was 292 (interquartile range: 146,438) g. There were significant differences in parafoveal and perifoveal thickness between the three study groups <2 years (n = 42), 2–5 years (n = 55), and >5 years (n = 13) (P < 0.05) which were evident as early as 2 years of usage. Further, the OCT parameters showed a significant correlation with perimetry changes (P < 0.001), macular thinning, color vision, and fundus changes. Conclusion: We demonstrate that SD-OCT and HVF 10-2 perimetry are complementary to each other and can be used to detect early retinal toxicity as early as 2 years of HCQ exposure.